Osteopetrosis: a rare case of portal hypertension - Amal Khsiba; Sahar Nasr; Lamine Hamzaoui; Moufida Mahmoudi; Asma Ben Mohamed; Manel Yaakoubi; Mouna Medhioub; Mohamed Moussadek Azouz (Future Science OA)
Osteopetrosis is a rare genetic bone disorder characterized by a defect in osteoclasts recruitment and function. Its manifestations are numerous and they mainly include skeletal and dental deformities, cranial nerve entrapment and infections. Over time, osteoclastic expansion invades bone marrow leaving little space for hematopoietic cells. As a result, extramedullary hematopoiesis takes place in the reticular system mainly in the spleen and liver. In these patients, portal hypertension can occur as a result of extramedullary hematopoiesis associated splenomegaly. We are reporting in this article a rare case of spontaneous bacterial peritonitis associated with portal hypertension in a patient with osteopetrosis.